Analysis of Prize Money and Performance between the Prize Money Ranking (1st to 60th) of Korea Ladies Professional Golf Players - Seo, Hankyo; Hwangbo, Sangwon; Park, Ikryeul (International Journal of Engineering and Technology, 2018)
The purpose of this study is to analyze the Prize Money and Performance of top 60 (1- 20th vs 21 - 40th vs 41- 60th) for the analysis of the Prize Money and Performance among the prize ranking of Korean Ladies Professional Golfers in 2017 using SPSS 23.0 program descriptive analysis and one-way ANOVA showed that the scoring average and putting average were â“‘group (21 - 40th)>â“group (1 - 20th)>â“’group (41 - 60th). Nonetheless, it is considered that the low prize money ranking is due to the fact that the prize money allocation method is overweighted in the group of 1 to 20th up to about 72%. However, as expected, the average birdie, green in regulation, par save, par break and recovery were as follows: â“group (1 - 20th)>â“‘group (21 - 40th)>â“’group (41 - 60th), the upper group showed higher prize money and good performance. However, it seems that appropriate consideration of the subgroups is necessary for the distribution of prize money. Because these tour professionals are experts we all recognize, they need proper treatment and economic support so that they can concentrate on the tour.Â Â